PENGGUNAAN UJI F UNTUK MENGETAHUI SIGNIFIKAN HUBUNGAN ANTARA PRODUKSI PENGUPASAN LAPISAN OVERBURDEN DAN LOSS TIME SERTA MENENTUKAN STANDARD ERRORNYA - Vitri Rospitasari; Diana Purwandari; Aditya Budi Nugraha (LPPM Universitas Bina Bangsa, 2022)
This research was conducted at PT. Starindo Sakti Award for 31 days. This study aims to determine whether or not there is a significant relationship between overburden stripping production and loss time. Because stripping of overburden is an activity that affects mining activities, the researcher is interested in analyzing every mining activity, especially in stripping the overburden layer at the mining front at PT. Starindo Sakti Award using a Kobelco SK-200 excavator. To determine whether or not the relationship between overburden stripping production and loss time is significant, the F test can be carried out. find out the deviation of the data. After conducting the F test, it turns out that the relationship between overburden stripping production and loss time is significant (very influential), as evidenced by the results Fhitung of 686 and Ftabel of 3.34 with a standard error of 5,8.